2007
DOI: 10.1128/jb.01132-06
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis and Identification of Streptococcus pyogenes Surface-Associated Proteins

Abstract: Streptococcus pyogenes is a gram-positive human pathogen that causes a wide spectrum of disease, placing a significant burden on public health. Bacterial surface-associated proteins play crucial roles in host-pathogen interactions and pathogenesis and are important targets for the immune system. The identification of these proteins for vaccine development is an important goal of bacterial proteomics. Here we describe a method of proteolytic digestion of surface-exposed proteins to identify surface antigens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
146
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(158 citation statements)
references
References 63 publications
11
146
0
1
Order By: Relevance
“…Conjecture exists in the scientific literature regarding the biological relevance and certitude of surface expression of anchorless proteins in GAS [5,30]. To validate our findings and to test protective vaccine efficacy of the selected anchorless surface proteins, full-length M1 protein, ADI, TF and FBA were adjuvanted with Complete Freund's Adjuvant (CFA) and used to subcutaneously immunize BALB/c mice and the survival recorded following lethal intraperitoneal M1 GAS challenge.…”
Section: Anchorless Proteins Elicit Protective Immunitymentioning
confidence: 82%
See 1 more Smart Citation
“…Conjecture exists in the scientific literature regarding the biological relevance and certitude of surface expression of anchorless proteins in GAS [5,30]. To validate our findings and to test protective vaccine efficacy of the selected anchorless surface proteins, full-length M1 protein, ADI, TF and FBA were adjuvanted with Complete Freund's Adjuvant (CFA) and used to subcutaneously immunize BALB/c mice and the survival recorded following lethal intraperitoneal M1 GAS challenge.…”
Section: Anchorless Proteins Elicit Protective Immunitymentioning
confidence: 82%
“…These authors also demonstrated considerable cross-protection of the 30-valent vaccine against non-vaccine M serotypes [4]. Recently, a series of independent studies have documented a class of GAS cell wall-associated or secreted metabolic enzymes that contain neither N-terminal leader sequences nor C-terminal cell wall anchors [5][6][7][8][9]. Perhaps because these molecules do not fit common categories of bacterial vaccine antigen, e.g.…”
mentioning
confidence: 99%
“…In total, taking into account the membrane protein fraction and the envelope-associated soluble protein fraction, one of the most remarkable findings of this work was the large amount of ribosomal proteins detected: 41 out of the 52 ribosomal proteins annotated in the B. longum NCC 2705 genome were identified. Ribosomal proteins are very often found associated with the cell surface in bacteria, and although they are thought to have a certain affinity for the inner leaflet of the membrane, they have also been detected on the bacterial surface exposed to the external medium (Severin et al, 2007;Tjalsma et al, 2008). In some cases it has even been demonstrated that ribosomal proteins are immunomodulatory for humans (Spence & Clark, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this, with the aim of determining the protein profile of the B. longum envelope, and as a first approach to undertaking deeper functional studies, we analysed different subcellular fractions. The application of gel-based and gel-free technologies, combined with high-throughput techniques, allowed us to identify 218 proteins; about 70 % of them were predicted to be, or were previously described as being, in the cell envelope of Gram-positive bacteria (Antikainen et al, 2007;Candela et al, 2007;Eymann et al, 2004;Granato et al, 2004;Jang & Hanash 2003;Kelly et al, 2005b;Nandakumar et al, 2005;Rivera-Amill et al, 2001;Rodríguez-Ortega et al, 2006;Schaumburg et al, 2004;Severin et al, 2007;Silveira et al, 2004;Tjalsma et al, 2008;Wolff et al, 2007). Furthermore, 48 of them are predicted to be integral membrane proteins (contain hypothetical transmembrane segments) and 30 of them have different extracytoplasmic sorting signals.…”
Section: Discussionmentioning
confidence: 99%
“…For intracellular proteome preparation (Malmström et al, 2012a), the bacterial cells were lysed using a bead-beater and centrifuged, and the supernatant was prepared for MS analysis, as subsequently described. For surface proteome preparation (Severin et al, 2007;Solis et al, 2010), surface-associated proteins were released by trypsination of the bacterial cells in a hypotonic solution. The trypsinated bacteria were gently centrifuged and the supernatant was prepared for MS analysis, as subsequently described.…”
Section: Introductionmentioning
confidence: 99%